Keterampilan Organisasi Kemahasiswaan Dalam Melakukan Komunikasi Profetik - Ramadhan, Abi Hasbi (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2017)
This paper discusses the importance of prophetic communication skills of student organizations on the management of the Indonesian Islamic Student Movement (PMII). One of the communication models offered in this paper is prophetic communication, namely communication based on prophetic characteristics. There are three main pillars in this prophetic communication, namely humanization, liberation, and transcendence. The implementation of the three pillars discussed in this paper is the importance of understanding the diversity and style of language used in communication. The prophetic communication of student organizations carried out by PMII in the UIN Sunan Gunung Djati Bandung campus environment if it works well can create a good impression from students in general. A good impression will lead to good loyalty which will encourage good use of information sources as well.